2009
DOI: 10.1128/jvi.00867-09
|View full text |Cite
|
Sign up to set email alerts
|

The Size of the Viral Inoculum Contributes to the Outcome of Hepatitis B Virus Infection

Abstract: The impact of virus dose on the outcome of infection is poorly understood. In this study we show that, for hepatitis B virus (HBV), the size of the inoculum contributes to the kinetics of viral spread and immunological priming, which then determine the outcome of infection. Adult chimpanzees were infected with a serially diluted monoclonal HBV inoculum. Unexpectedly, despite vastly different viral kinetics, both high-dose inocula (10 10 genome equivalents [GE] per animal) and low-dose inocula (10 0 GE per anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
290
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(302 citation statements)
references
References 35 publications
9
290
3
Order By: Relevance
“…Previous studies of HBV clearance in infected patients (3) and chimpanzees (9,10,11,18) have demonstrated that CD4 + T cells and CD8 + T cells are required for elimination of HBV from the liver during natural infection. An essential role for Fas and TNFR1 in the clearance of HBV is less obvious.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of HBV clearance in infected patients (3) and chimpanzees (9,10,11,18) have demonstrated that CD4 + T cells and CD8 + T cells are required for elimination of HBV from the liver during natural infection. An essential role for Fas and TNFR1 in the clearance of HBV is less obvious.…”
Section: Resultsmentioning
confidence: 99%
“…Our current understanding is based to a large extent on comparison of the immune responses mounted against HBV in patients who clear and who fail to clear HBV (3), experiments in which potential effectors of clearance (e.g., HBsAg-specific CD8 + T cells, recombinant IFN-γ and TNF-α) have been adoptively transferred to or induced in HBV transgenic mice (4)(5)(6)(7)(8), and a limited number of experiments conducted in HBVinfected chimpanzees (9,10,18). Collectively, these studies have led to the current model for clearance of acute HBV infection, namely (i) that viral clearance during HBV infection is associated with entry of CD8 + T cells into the liver, the production of IFN-γ, and the induction of inflammatory liver disease (reviewed in ref.…”
mentioning
confidence: 99%
“…5 In short, HBV-specific CTL activity has the key role in controlling the outcome of HBV infection because the magnitude of the T-cell response is a critical factor in determining viral control. [6][7][8][9] CD8 þ T cells recognize antigenic peptides presented by MHC I molecules on the surface of APCs or target cells. Folding of MHC I molecules and loading with an appropriate peptide require the assistance of a number of chaperones present in the endoplasmic reticulum (ER), including protein disulfide isomerase, calnexin, calreticulin, ERp57, Tapasin, and the TAP, the latter four forming the peptide-loading complex (PLC).…”
mentioning
confidence: 99%
“…5 In short, HBV-specific CTL activity has the key role in controlling the outcome of HBV infection because the magnitude of the T-cell response is a critical factor in determining viral control. [6][7][8][9] …”
mentioning
confidence: 99%
“…[17][18][19] In a chimpanzee model of acute HBV infection, early activation of CD4 1 T cells correlated with an influx of HBV-specific CD8 1 T cells into the liver, and animals depleted of CD4 1 T cells became persistently infected when inoculated with a dose of HBV. 15,20 These results indicated that the induction of efficient antiviral cytotoxic Tlymphocyte responses depend on early CD4 1 T-cell priming to HBV infection.…”
Section: Function Of Il-21 In Cellular Immune Responsesmentioning
confidence: 84%